Aspiration Strain and Mental Health: The Education-Contingent Role of Religion - DeAngelis, Reed T. (Journal for the scientific study of religion, 2018)
This study examines whether dimensions of religious involvement (i.e., perceived divine control, private religious practices, and religious social integration) buffer associations between aspiration strain and mental health outcomes (i.e., psychological distress, loneliness, and optimism). We also test three-way interactions to determine whether the stress-buffering effects of religious involvement are amplified among undereducated persons. We test our hypotheses with cross-sectional survey data from Vanderbilt University's Nashville Stress and Health Study (2011-2014), a probability sample of non-Hispanic white and black adults from Davidson County, Tennessee (n = 1,252). Results from multivariate regression models confirmed: (1) aspiration strain was positively associated with psychological distress and loneliness, and negatively associated with optimism; and (2) religious involvement attenuated these associations, but only for respondents with less than or equal to a high school education. We discuss the implications and limitations of our findings and outline avenues for future research.